Pressure induced topological and structural phase transitions in 1T-TiSe2: a Raman study. (22nd February 2019) - Rajaji, V; Janaky, S; Sarma, Saurav Ch.; Peter, Sebastian C; Narayana, Chandrabhas
Abstract: High pressure Raman spectroscopy studies on 1T-TiSe2 were carried out up to 20.5 GPa. Based on the anomalies in phonon linewidth (lifetime) and phonon frequency of A 1g mode, we observe three transitions at 2.5 GPa, 6.0 GPa and 15 GPa. The transitions at 2.5 and 6.0 GPa are the two topological phase transitions consistent with the theoretical prediction by Zhu et al in 1T-TiSe2 under pressure, namely, a topological trivial to non-trivial transition ( Z 2 = 1) and topological non-trivial to trivial transition ( Z 2 = 0). The trigonal (1T) phase of TiSe2 is stable up to 15 GPa beyond which it undergoes structural transition as seen from the appearance of new Raman modes. There is a coexistence of the 1T and the new high-pressure phase up to 19 GPa. The structural transition is completely reversible as seen from the appearance of 1T phase Raman spectra upon release of the pressure.